Penerepan Metode Waterfall Dalam Pembuatan Sistem Informasi Akuntansi Persediaan Barang Sekali Pakai Pada Dinas Kesehatan Provinsi Kalimantan Barat - Sabaruddin, Raja; Murni, Sri; Alfaridzi, Fiqih (Jurnal Sistem Informasi Akuntansi, 2023)
Information technology is now showing many major changes as well as its influence, in the accounting field in particular it can help company management as well as in government, one of the information system activities that can be facilitated is the disposable inventory system. The West Kalimantan Provincial Health Office realized that the recording of inventory of disposable goods was still done manually or not computerized, thus allowing for errors in recording incoming goods, outgoing goods, stock of goods, and making reports. The research method used is data collection, observation, interviews, literature study, system design, analysis of software requirements for system design and software, implementation and unit testing. The design of this website is built using the waterfall model development method and the PHP programming language and utilizes the MySQL database as a database server. The results of this study are the right solution to overcome the problems that exist in the West Kalimantan Provincial Health Office. With a computerized system will be very helpful in supporting all activities so as to produce effective and efficient work.